TrkA activation in the rat visual cortex by antirat trkA IgG prevents the effect of monocular deprivation - Pizzorusso, Tommaso (1999)
It has been recently shown that intraventricular injections of nerve growth factor (NGF) prevent the effects of monocular deprivation in the rat. We have tested the localization and the molecular nature of the NGF receptor(s) responsible for this effect by activating cortical trkA receptors in monocularly deprived rats by cortical infusion of a specific agonist of NGF on trkA, the bivalent antirat trkA IgG (RTA-IgG). TrkA protein was detected by immunoblot in the rat visual cortex during the critical period. Rats were monocularly deprived for 1 week (P21–28) and RTA-IgG or control rabbit IgG were delivered by osmotic minipumps. The effects of monocular deprivation on the ocular dominance of visual cortical neurons were assessed by extracellular single cell recordings. We found that the shift towards the ipsilateral, non-deprived eye was largely prevented by RTA-IgG. Infusion of RTA-IgG combined with antibody that blocks p75(NTR) (REX), slightly reduced RTA-IgG effectiveness in preventing monocular deprivation effects. These results suggest that NGF action in visual cortical plasticity is mediated by cortical TrkA receptors with p75(NTR) exerting a facilitatory role.